2016
DOI: 10.1016/j.eurger.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Calf circumference predicts mobility disability: A secondary analysis of the Mexican health and ageing study

Abstract: Introduction Calf circumference is a surrogate measurement of muscle mass. However, there is scarce evidence on its validity in predicting adverse outcomes such as mobility disability. The aim of this report is to determine if calf circumference could predict incident mobility disability in Mexican 60-year or older adults. Methods This is a secondary analysis of the Mexican Health and Aging Study and in particular of its two first waves. Sixty-year or older adults without mobility disability in the first ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
(34 reference statements)
0
19
0
1
Order By: Relevance
“…In Taiwan, the decrease in CP (26) increased the risk of death in men by 1.30 (RR: 1.22-1.71) and in women by 1.38 (RR: 1.15-1.48) . Although studies (23)(24)(25)(26) have shown that decreased CP increases the likelihood of decreased muscle mass, a study with elderly in Mexico (24) showed that CP increase (> 38 cm) had an independent association with disability, suggesting that the fat tissue may still impact muscle function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Taiwan, the decrease in CP (26) increased the risk of death in men by 1.30 (RR: 1.22-1.71) and in women by 1.38 (RR: 1.15-1.48) . Although studies (23)(24)(25)(26) have shown that decreased CP increases the likelihood of decreased muscle mass, a study with elderly in Mexico (24) showed that CP increase (> 38 cm) had an independent association with disability, suggesting that the fat tissue may still impact muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of identifying elderly patients with reduced muscle mass through CP is reinforced by studies that have evaluated their ability to predict mortality (23)(24) and disability (24)(25) and need for care (26) . In Taiwan, the decrease in CP (26) increased the risk of death in men by 1.30 (RR: 1.22-1.71) and in women by 1.38 (RR: 1.15-1.48) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAC possibly represents the skeletal muscle mass; however, in patients with knee osteoarthritis, calf circumference may represent fat accumulation. Perez‐Zepeda and Gutierrez‐Robledo also found that high calf circumference could reflect a greater amount of subcutaneous fat in patients with high BMI. The introduction of handgrip strength in our study as a variable may increase the equation's complexity.…”
Section: Discussionmentioning
confidence: 86%
“…Calf circumference has been proven to be positively correlated to skeletal muscle mass, and might thus be a potential indicator of decreased muscle mass in clinical practice as an alternative to imaging modalities and bioimpedance analysis. 12,13 However, although calf circumference has been endorsed in as a reliable indicator for evaluating muscle mass, 8,9,14 its use remains controversial. 10 Edema can develop from malnutrition, and renal, hepatic and cardiac diseases, and as a side-effect of medications that increase fluid accumulation in the body; 15,16 thus, edema can increase calf circumference.…”
Section: Introductionmentioning
confidence: 99%